Pengaruh Komposisi Kompon Ban Dengan Batikan Zig-Zag Terhadap Koefisien Gesek Banpada Lintasan AspalBasah Dan Kering - Dwi Rahmanto, Ary, Ir. Pramuko Ilmu Purbo Putro, MT, Supriyono, Ph.D (2016)
Human need quick mobility will be safe and comfortable at this time is very important. Dizaman modern already like this man dituntutut more creative in order to adjust the age. Needs in terms of transport became a necessity for human beings. The use of motor vehicles such as motorcycles, cars and buses are familiar among the public. Because in human keseharianya sure to use means of transport like this. One of the components supporting the above means of transportation is the tires. Ban is an important part of the vehicle as above. Security and comfort factor is largely determined by the composition of the existing daam ban. Research objectives here is to find out the composition of compounds in the manufacture of tires, as well as the strong pull of mengeahui and violence on the tires The materials used in the manufacture of compounds is natural rubber and synthetic rubber SBR RSS mixed with chemicals of black carbon, white oil, Zno, strearic acid, prafin wax, MBTS, resin cumaron and sulfur, mixed use of rolling mixing to form a sheet. Rheometer testing done to find out the value of maturity, after which the vulcanization mold with zig-zag batikan at vulkanizing press machine. Testing the hardness of shore hardness test using a tester with standard SNI with the result compounds market 60, compounds 1, 2, 3 respectively 68.33, 69, 74. Tensile testing using test rubber testing equipment with the standard SNIdengan result compounds market 205.163, compounds 1, 2, 3 respectively 178.64, 141.007, 111.737. Testing of friction coefficients by using the tool test brake shoes that have been engineered to grip the tire with the results of the test compounds market 0.773, compounds 1, 2, 3 respectively 0.756, 0.751, keringdan thermal conditions 0.725 market 0.727, compounds 1, 2, 3 respectively 0.702, 0.693, 0.685 in wet conditions. Keywords: Compounds, black carbon and sulfur, the coefficient of friction